Development of Cooperative Learning (STAD) to Enhance Learning Achievement on Integer Calculations for Grade 7 Students at the Demonstration Secondary School of Savannakhet Teacher Training Collegeions for Grade 7 Students at the Demonstration Secondary School of Savannakhet Teacher Training College - KEOMOUNGKHOUN, Daomanolack (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objectives of this research were: 1) to determine the quality and evaluate the efficiency of lesson plans based on the Student Team Achievement Divisions (STAD) cooperative learning technique to enhance the academic achievement on "Integer Calculation" of Grade 7 students at the Demonstration Secondary School of Savannakhet Teacher Training College, based on the 75/75 efficiency criteria; 2) to compare students' academic achievement before and after the implementation of the STAD-based instruction; and 3) to study student satisfaction toward the STAD cooperative learning method. The sample group consisted of 36 Grade 7 students, selected through purposive sampling. The research instruments included STAD-based lesson plans, an academic achievement test, and a satisfaction questionnaire. Data were analyzed using SPSS (version 20.0) to calculate percentage (%), mean ( ), standard deviation (SD), efficiency criteria (E1/E2), and Paired Sample t-test. The findings revealed that: 1) The efficiency of the STAD cooperative learning lesson plans (E1/E2) was 80.50/82.00, which exceeded the established 75/75 threshold. 2) The students' post-test academic achievement was significantly higher than the pre-test at a 0.001 level of statistical significance. 3) Overall student satisfaction toward the STAD cooperative learning was at the highest level ( = 4.65, SD = 0.48).